The effects of fermentation with lactic acid bacteria on the antioxidant and anti-glycation properties of edible cyanobacteria and microalgae. (January 2021) - Kaga, Yuko; Kuda, Takashi; Taniguchi, Miyu; Yamaguchi, Yuji; Takenaka, Hiroyuki; Takahashi, Hajime; Kimura, Bon
Abstract: Cyanobacteria and microalgae-derived food supplements have gained attention in recent times, owing to their antioxidant, hypolipidemic, and anti-obesity effects. In the present study, we analysed the antioxidant and anti-glycation activities of 12 aqueous extract solutions (AESs) of 10 species of cyanobacteria and microalgae. The AESs of the microalgae Dunaliella tertiolecta and Pleurochrysis carterae showed strong ferric-reducing powers, superoxide anion (O2 − ) radical scavenging capacity, and anti-glycation activity in a bovine serum albumin (BSA)-fructose model. Wild Nostoc commune (cyanobacteria) and sake lees cultured Euglena sp. (microalga) could be fermented by Lactococcus lactis subsp. lactis Uruma-SU1, whereas normal cultured N. commune and Euglena could not. The O2 − radical-scavenging capacity and anti-glycation activity in the BSA-methylglyoxal model of the fermented wild N. commune and sake lees cultured Euglena samples were higher than those of the other samples. As advanced glycation end products and reactive oxygen species induce age-related diseases, our study illustrates the health-promoting properties of D. tertiolecta and P. carterae and lactic acid bacteria-fermented wild N. commune and sake lees cultured Euglena sp.; moreover, it communicates their importance as nutritional food materials. Graphical abstract: Image 1 Highlights: D. tertiolecta and P. carterae showed strong Fe-reducing powers and O2 − radical scavenging capacity. D. tertiolecta and P. carterae showed high anti -glycation activity in BSA-Fru model. L. lactis Uruma-SU1 fermented wild N. commune (IKw) and sake lees cultured Euglena sp (EGs). Fermentation augmented O2 − radical-scavenging capacity of IKw and EGs samples. Fermentation augmented anti -glycation activity of IKw and EGs samples in BSA-MGO model.